Microscopic analysis of dog dental pulp after pulpotomy and pulp protection with mineral trioxide aggregate and white Portland cement Análise microscópica da polpa dental de cães após pulpotomia e proteção pulpar com agregado de trióxido mineral e cimento Portland branco - Renato Menezes; Clóvis Monteiro Bramante; Roberto Brandão Garcia; Ariadne Letra; Vanessa Graciela Gomes Carvalho; Everdan Carneiro; Sérgio Brunini; Rodrigo Cardoso Oliveira; Giovana Calichio Canova; Fernanda Gomes de Moraes (University of São Paulo, 2004)
Considering previous studies on the similarity between the chemical composition of the mineral trioxide aggregate and the Portland cement, the purpose of this study was to investigate the pulp response of dog's teeth after pulpotomy and direct pulp protection with MTA Angelus and white Portland cement. Thirty eight pulp remnants were protected with these materials. One hundred and twenty days after treatment, the animals were sacrificed and the specimens removed and prepared for histological analysis. Both materials demonstrated the same results when used as pulp capping materials, inducing hard tissue bridge formation and maintaining pulp vitality in all specimens. The MTA Angelus and the white Portland cement showed to be effective as pulp protection materials following pulpotomy. Considerando estudos anteriores sobre a similaridade entre a composição química do agregado de trióxido mineral e o cimento Portland, o objetivo deste estudo foi investigar a resposta pulpar de dentes de cães após pulpotomia e proteção pulpar direta com MTA Angelus e cimento Portland branco. Trinta e oito remanescentes pulpares foram recobertos com esses materiais. Cento e vinte dias após o tratamento, os animais foram sacrificados e os espécimes removidos e preparados para análise histológica. Ambos os materiais demonstraram os mesmos resultados quando utilizados como materiais de capeamento pulpar, induzindo a formação de ponte de tecido mineralizado e mantendo a vitalidade pulpar em todos os espécimes. Ambos matérias se mostraram efetivos como protetores pulpares após pulpotomia em dentes de cães.